Pemikiran Imam Al-Ghazali dalam Kilas Sejarah: Analisis Bibliometrik dalam Kontribusinya Terhadap Pendidikan - Hamdi, Hamdi; Hartati, Zainap; Nasir, Muhammad; Syi'bul Huda, Ali Anhar (Jurnal Media Informatika, 2025)
The purpose of this study is to provide recommendations for further research related to the flashback of Imam Al-Ghazali's thoughts through bibliometric analysis. The research uses a qualitative approach and bibliometric analysis. Data source from google scholar, the publish or perish (PoP) application with 100 articles as a sample with the keyword Imam Al-Ghazali's thoughts in the publication time range of 2020-2024 resulted in 100 articles analyzed using the VOSViewer application version 1.6.20. The results of this study show that based on searches through the google scholar database (search time span 2020-2024) the development of publications has gradually increased, but has decreased in 2020, 2021, and 2024. The development of research on Imam Al-Ghazali's thought occurred the most in 2023, namely 26 publications, and decreased in 2021 to only 12 publications relevant to the topic of Imam Al-Ghzali's thought. The research shows the productivity of researchers who examine the topic of Imam Al-Ghazali's thought consisting of 6, namely Janwari, Jubaidah, Putri, yasin, Faizin, and Padhil. Then, based on the results of network analysis, overlay, and density vizualitation, in general, previous research only focused on researching Imam Al-Ghazali's thinking broadly, but did not associate Imam Al-Ghazali's thinking with character education, study, thought, and perspective. So that the findings are highly recommended for future researchers.